(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The study reports the fungus flora isolated from three anthills of Formica lugubris Zett. in a pine -wood (Pinus nigra) in the Ligurian Apennine, where ants have been introduced. The research, which was carried out throughout a whole year, assessed the variations of the found fungi in relation to the biological cycle of Formica lugubris. Fifty-four fungal species were recorded; the commonest ones were briefly discussed: they are mostly entomogenous and saprophytic fungi. The latter are associated to litter and soil debris.